Germline genetics of prostate cancer. (3rd June 2022) - Khan, Hiba M.; Cheng, Heather H.
Abstract: Background: An important fraction (>/~10%) of men with high‐risk, localized prostate cancer and metastatic prostate cancer carry germline (heritable) pathogenic and likely pathogenic variants (also known as mutations) in DNA repair genes. These can represent known or suspected autosomal dominant cancer predisposition syndromes. Growing evidence suggests that pathogenic variants in key genes involved in homologous recombination and mismatch DNA repair are important in prostate cancer initiation and/or the development of metastases. Aims: Here we provide a comprehensive review regarding individual genes and available literature regarding risks for developing prostate cancer, and discuss current national guidelines for germline genetic testing in the prostate cancer population and treatment implications. Results: The association with prostate cancer risk and treatment implications is best understood for those with germline mutations of BRCA2, with emerging data supporting associations with ATM, CHEK2, BRCA1, HOXB13, MSH2, MSH6, PALB2, TP53 and NBN. Treatment implications in the metastatic castration resistant prostate cancer setting include rucaparib and olaparib, and pembrolizumab with potential clinical trial opportunities in earlier disease settings. Discussion: The data summarized in this review has led to the expansion of national guidelines for germline genetic testing in prostate cancer. We review these guidelines, and discuss the importance of cascade genetic testing of relatives, diverse populations with attention to inclusion, as well as prostate cancer screening updates and clinical trial opportunities for men who carry genetic risk factors for prostate cancer.